A Great Deliverance - George, Elizabeth, 1949-, author 535163 (Toronto : Bantam Books, 1989)
Fat, unlovely Roberta Teys is found beside her father's headless corpse, wearing her best dress and with an axe in her lap. Her first words are: 'I did it. And I am not sorry' and she refuses to say more. Inspector Thomas Lynley and DS Barbara Havers are sent by Scotland Yard to solve this particularly gruesome murder. And as they navigate their way around a dark labyrinth of secret scandals and appalling crimes, they uncover a series of shocking revelations that shatter the facade of the peaceful Yorkshire village.